Perbandingan Metode Moving Average dan Single Exponential Smoothing Pada Peramalan Inflasi Kota Purwokerto - Chandra, Novita Eka; Rohmaniah, Siti Alfiatur (Jurnal Matematika; Vol 12 No 1 (2022)DO - 10.24843/JMAT.2022.v12.i01.p148, 2022)
The rate of inflation that goes up and down can lead to economic instability. To overcome this, it is necessary to forecast the value of inflation in the coming year, so that the government can make decisions in regulating economic policy. The data used in this research is the inflation data for the city of Purwokerto for 6 years. Based on the data plot, it can be seen that the data can be predicted using the Moving Average and Single Exponential Smoothing methods. The purpose of this study is to compare the two forecasting methods and determine the best method based on the error size value. From the analysis, it is found that the Single Exponential Smoothing method is better used in forecasting than the Moving Average method, because the MAPE, MSD and MAD values ??are smaller. The results of inflation forecasting for the city of Purwokerto in 2018 rose by 0.44 percent.